Illocutionary speech acts on Donald Trump's speech in addressing the covid-19 breakout - Neni Nurkhamidah (Universitas Islam Malang, 2020)
This research aims at finding out the illocutionary speech act on one Donald Trump's speech in addressing the COVID-19 outbreak. The speech is conducted at Oval Office in 11 March 2020. This is a qualitative research that implemented the theory of speech act by Searle (1979). Result shows that Trumps made all five categories of illocutionary speech act with different amount of each category. The most utterances he made is assertive (54%). The type of assertive in his speech is boasting, claiming, describing, informing, and stating. The next category is commissive (29%) that consist of promising, and planning. In directive categories (15%) the utterance he made is commanding and advising. And Expressive (1%) consist of thanking and the last is declarative (1%) can be seen from his utterance when he blessed the audiences.